ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PAJAK UMKM TERHADAP UU PERPAJAKAN NOMOR 28 TAHUN 2007 - vonnytiara narundana; Abdurrahman Saputra (Universitas Bandar Lampung (UBL), 2022)
There are many news in the mass media about the crime of bribery cases in the taxation scope and state budget waste may give a negative perception for WP toward the goverenment’s efforts to intensify tax collection and tax management transparency. This study aims to determine whether the benefits of having NPWP, sanctions, and the perception of taxpayers compliance of micro and small entrepreneurs in the city of Bandar Lampung related tax law number 28 of 2007. The sample in this study are small and micro entrepreneurs in the city of Bandar Lampung which are furniture business, home industries (manufacturing business of tofu, pempek, chips), convections, workshop, bakery, cafe, restaurant, panglong woods, and shops. The data used are primary data by direct surveys using the media poll/questionnaires. Data analysis tool that is used in this research is descriptive analysis.The results showed that the benefits of having NPWP, sanctions, and the perception of taxpayers effect to the tax compliance of small and micro businesses to obey tax laws related to tax law number 28 of 2007.